BEHAVIORAL INTENTION OF ISLAMIC PEER-TO-PEER LENDING SERVICES USERS - Mega Rachma Kurniaputri; Nur Fatwa (Universitas Airlangga, 2022)
The fintech lending industry, as in non-bank financial institutions in Indonesia, has faced several problems, such as low financial literacy, constraints on the information system, weak scoring system, users data leakage, technology gaps with Islamic banks, and cases of default that make lenders disappointed and share it through social media. Although there are many problems, it does not reduce the intention of the lenders to lend their money through peer-to-peer lending as an alternative investment place. This research uses a quantitative descriptive method with the Partial Least Square - Structural Equation Modeling (PLS-SEM) technique. The study is conducted on 250 lenders in Indonesia who lend through Islamic peer-to-peer lending. Based on the results, lenders' intention is influenced by factors of effort expectancy, habit, and hedonic motivation. The lenders found that lending their money will improve their profit and make it easy to use. Meanwhile, facilitating conditions, habits, and behavioral intentions directly affect user behavior to continue to choose the Islamic peer-to-peer lending service that is already being used. The acceptance and use of lenders to use Islamic peer-to-peer lending are influenced by effort expectancy, habit, hedonic motivation, facilitating conditions, and behavioral intentions. This study is expected to be a recommendation for the financial technology industry to improve its services and facilities for users, particularly for lenders. In addition, this research can be an additional reference for regulators to make regulations related to Islamic financial technology, particularly for lenders in fintech lending.